Pengalaman Mahasiswa dalam Menggunakan Artificial Intelligence untuk Mendukung Belajar - Nyak Salsabilla; Sri Nurhayati Selian (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The development of artificial intelligence (AI) has brought about significant changes in higher education, particularly in how students acquire, understand, and manage academic information. This study aims to deeply understand students' experiences using AI as a learning tool and explore how they interpret the technology's role in supporting academic activities. A qualitative phenomenological approach was used, with three informants selected purposively from various study programs actively using AI. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The results show that students view AI as an effective tool for improving learning efficiency, deepening conceptual understanding, and motivating them to be more independent and creative. However, challenges were also identified, including dependence on technology, doubts about the accuracy of information, and concerns about academic ethics violations such as digital plagiarism. Student experiences also demonstrate that AI plays a dual role as both a learning tool and a cognitive partner in the modern learning process. Therefore, the use of AI needs to be directed wisely and accompanied by strong digital literacy to balance technological convenience and the development of critical thinking skills. These findings emphasize the importance of adaptive, humanistic, and ethical learning strategies in the era of digital higher education transformation.